2018
DOI: 10.1186/s13007-018-0339-y
|View full text |Cite
|
Sign up to set email alerts
|

A low-cost method to rapidly and accurately screen for transpiration efficiency in wheat

Abstract: BackgroundWheat (Triticum aestivum L.) productivity is commonly limited by the availability of water. Increasing transpiration efficiency (biomass produced per unit of water used, TE) can potentially lead to increased grain yield in water-limited environments (‘more crop per drop’). Currently, the ability to screen large populations for TE is limited by slow, low-throughput and/or expensive screening procedures. Here, we propose a low-cost, low-technology, rapid, and scalable method to screen for TE. The metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…That is, TE FC can be observed under soil moisture at field capacity or even saturated soil or water culture conditions. The situation is in accordance with Fletcher et al (2018), who measured the TE of wheat cultivated with sufficient water. Additionally, parameter b is significantly related to TE FC (Figure 9), b = 0.1806 × TE FC -1.2444 (R 2 = 0.7375, n = 12, p ≤ 0.01).…”
Section: Usage Of the Transpiration Efficiency-relative Soil Water Co...supporting
confidence: 86%
See 3 more Smart Citations
“…That is, TE FC can be observed under soil moisture at field capacity or even saturated soil or water culture conditions. The situation is in accordance with Fletcher et al (2018), who measured the TE of wheat cultivated with sufficient water. Additionally, parameter b is significantly related to TE FC (Figure 9), b = 0.1806 × TE FC -1.2444 (R 2 = 0.7375, n = 12, p ≤ 0.01).…”
Section: Usage Of the Transpiration Efficiency-relative Soil Water Co...supporting
confidence: 86%
“…As is already known, variation in soil types (Ritchie, 1972;Tfwala et al, 2021), agronomic strategies such as fertilization (Hernandez et al, 2021) and organic amendments (Wang et al, 2021), growth regulators (Li et al, 2017(Li et al, , 2020, and environmental factors such as temperature (Vadez and Ratnakumar, 2016), atmospheric CO 2 concentration (Tausz-Posch et al, 2012;Christy et al, 2018) and VPD [atmospheric vapor pressure deficit, (Vadez et al, 2014)] might change the TE of a given cultivar. Previous studies have also reported alterations in the ranking of TE among varieties resulting from some of these factors (Zhao et al, 2008;Fletcher et al, 2018). Setting out to study the effects of such factors on the TE-RSWC curve and the underlying mechanisms will help us to understand changes in TE due to exposure to various surroundings.…”
Section: Uncertainties Of the Transpiration Efficiency-relative Soil ...mentioning
confidence: 97%
See 2 more Smart Citations
“…Evaporation (E) refers to the loss of water from the soil where the crop is placed. Specific literature has been used and methods for determining transpiration (T) (Fletcher et al, 2018) or evapotranspiration (Lu et al, 2018;Kenjabaev et al, 2020) in wheat have been assimilated. Using the CROPWAT model (Smith et al, 2002) and the Mark Marsalis model (ACES, 2018), we were able to simulate the required daily plant consumption over the entire vegetation period.…”
Section: Introductionmentioning
confidence: 99%